Establishment of Borneo Literature Bureau and its role in the publication of Chinese edition of Dolphin magazine in the Cold War era - Wong, Kee Lian (2018)
Borneo Literature Bureau (BLB) was established by the British colonial government of Sarawak on 15 September 1958, at a time when Southeast Asia was at the height of the Cold War era. According to BLB’s annual report 1960, there were three objectives for its establishment, i.e. (i) assisting the government departments in publishing technical, semi-technical and educational books; (ii) encouraging creative writings by local writers apart from distributing and selling their works; and (iii) setting up sales networks for books and magazines to promote suitable reading materials published locally or abroad. By 1970, after Sarawak was involved in the formation of Malaysia, BLB had another new objective added, i.e. assisting the government to encourage the comprehensive use of Bahasa Malaysia among the people. Apparently, BLB’s works in publication, promotion of local creative writings and sale of books and magazines as well as its Malaysianised transformation were undertaken during the period when the Cold War era went through its peak and decline, thus constituting a special cultural phenomenon of Borneo in the 1960s and 1970s. In close to 20 years of its publication, BLB had gone through major events such as the Cold War struggle, the colonial government rule, the turbulent period of anti-colonialism, anti-imperialism and anti-Malaysia movements as well as the formation of Malaysia. The Chinese edition of Dolphin magazine was published amidst such a background and it was then the only student and youth magazine edited and published by BLB. Its period of publication lasted roughly from November 1961 to September 1977, with a total of 191 issues published. The magazine’s target readers included Chinese school students in upper primary classes and junior secondary classes. Besides, students of senior secondary classes and schoolleavers (graduates or dropouts) were also important potential readers. Dolphin magazine had rich contents of in-depth significance including introductions to local places as well as various ethnic groups and customs, folklore, historical stories, Malay and English language pages, mathematics page, general knowledge quiz and students’ creative writings, interspersed with photographs as well as illustrations and comic drawings.Judging from its overall sales, the magazine was well received in the cultural and educational sectors as well as among the youths. It was also the major contributor to the sales performance of BLB. This thesis attempts to examine the creation and publication of Dolphin magazine in the context of Cultural Cold War, to interpret the apparent and hidden meanings of its publication based on its editorial styles and contents and to trace the special missions bestowed by the British colonial government on BLB and the Chinese edition of Dolphin magazine. Results of this study reveal that the main objective of the British colonial government’s establishment of BLB and publication of Dolphin magazine was to contend with the leftist literature and cultural activities that were very popular by then, and to fill the vacuum due to the shortage of reading materials in the market caused by the government’s policy for banning books. At the same time, the government was striving to impart to the Chinese youths the local consciousness of Borneo, to nurture their patriotic emotion towards Malaysia as a nation and to encourage them to support, identify with and be loyal to the newly formed Malaysian government so that they would not be influenced by the leftist communist political movement.